Situación actual de la producción y rentabilidad de los pequeños productores de banano en la zona de Los Ríos - Ramírez Sande, William Gustavo (2023)
The current situation of production and profitability of small banana producers in the Los Ríos area is a cause for concern and study. These farmers face various challenges that impact their ability to maintain the profitability of their operations. Factors such as climatic conditions, pest and disease management, market competition and production costs influence the production and profits of these farms. An in-depth analysis of each farm is required to identify the specific problems it faces, as well as opportunities for improvement. This could include implementing more efficient agricultural practices, adopting modern technologies, diversifying crops, or accessing government support programs. The profitability of these small-scale banana farms is essential to the economic well-being of the region, and existing challenges need to be addressed to ensure the long-term sustainability of their operations.